Field-scale testing and numerical investigation of soil-boulder interaction under vehicular impact using FEM and coupled FEM-SPH formulations. Issue 1 (March 2016) - Reese, Lynsey; Qiu, Tong; Linzell, Daniel; Rado, Zoltan
A computational approach that couples the Finite Element Method and the Smoothed Particle Hydrodynamics method may be advantageous for simulating the response of complex, physical systems involving large deformations. However, comparisons of this modeling technique against field-scale test data are remarkably sparse in literature. This study presents three field-scale tests involving vehicular impact into three landscape vehicular anti-ram barriers. Each barrier consisted of a single boulder embedded in compacted American Association of State Highway and Transportation Officials soil and physical testing resulted in one of the following outcomes: minimal boulder/soil movement (Test 1), moderate boulder/soil movement (Test 2), and severe boulder/soil movement and vehicle override (Test 3). For each test, two LS-DYNA models were developed: a model using a traditional finite element method approach for the entire soil region along with a model using a hybrid finite element method-smoothed particle hydrodynamics approach where the near-field soil region was simulated using smoothed particle hydrodynamics. For Tests 1 and 2, both the traditional finite element method approach and the hybrid finite element method-smoothed particle hydrodynamics approach were able to accurately match data collected from the field tests. However, for Test 3, the finite element method-only approach was not able to accurately predict the global response of the system under vehicular impact. On the other hand, the hybrid finite element method-smoothed particle hydrodynamics approach was able to capture global response of the system including boulder rotation, soil upheaval, and vehicle override.